Interfering in the ALK1 Pathway Results in Macrophage-Driven Outward Remodeling of Murine Vein Grafts - de Jong, Alwin; Sier, Vincent Q.; Peters, Hendrika A. B.; Schilder, Natalia K. M.; Jukema, J. Wouter; Goumans, Marie José T. H.; Quax, Paul H. A.; de Vries, Margreet R. (Frontiers in Cardiovascular Medicine, 2022)
Aims Vein grafts are frequently used to bypass coronary artery occlusions. Unfortunately, vein graft disease (VGD) causes impaired patency rates. ALK1 mediates signaling by TGF-β via TGFβR2 or BMP9/10 via BMPR2, which is an important pathway in fibrotic, inflammatory, and angiogenic processes in vascular diseases. A role of the TGF-β pathway in VGD is previously reported, however, the contribution of ALK1 signaling is not known. Therefore, we investigated ALK1 signaling in VGD in a mouse model for vein graft disease using either genetic or pharmacological inhibition of the Alk1 signaling. Methods and results Male ALK1 heterozygous (ALK1+/-), control C57BL/6, as well as hypercholesterolemic ApoE3*Leiden mice, underwent vein graft surgery. Histologic analyses of ALK1+/- vein grafts demonstrated increased outward remodeling and macrophage accumulation after 28 days. In hypercholesterolemic ApoE3*Leiden mice receiving weekly ALK1-Fc injections, ultrasound imaging showed 3-fold increased outward remodeling compared to controls treated with control-Fc, which was confirmed histologically. Moreover, ALK1-Fc treatment reduced collagen and smooth muscle cells accumulation, increased macrophages by 1.5-fold, and resulted in more plaque dissections. No difference was observed in intraplaque neovessel density. Flow cytometric analysis showed increased systemic levels of Ly6CHigh monocytes in ALK1-Fc treated mice, supported by in vitro increased MCP-1 and IL-6 production of LPS-stimulated and ALK1-Fc-treated murine monocytes and macrophages. Conclusion Reduced ALK1 signaling in VGD promotes outward remodeling, increases macrophage influx, and promotes an unstable plaque phenotype.